Detection of Low-Level Fosfomycin-Resistant Variants by Decreasing Glucose-6-Phosphate Concentration in Fosfomycin Susceptibility Determination - Guillermo Martín-Gutiérrez; Fernando Docobo-Pérez; Jose Manuel Rodríguez-Martínez; Alvaro Pascual; Jesús Blázquez; Jeronimo Rodriguez-Beltrán (MDPI AG, 2020)
Mutations that confer low-level fosfomycin resistance (LLFR) but not clinical resistance in Escherichia coli are increasingly reported. LLFR strains can become clinically resistant under urinary tract physiological conditions or may act as gateways for highly resistant subpopulations by the selection of additional LLFR mutations. Nevertheless, most LLFR strains are impossible to detect under routine fosfomycin susceptibility determinations. Here, we have explored the possibility of detecting LLFR variants by reducing glucose-6-phosphate (G6P) concentration in fosfomycin susceptibility testing for E. coli strains. As a proof of concept, fosfomycin minimal inhibitory concentrations (MICs) and disk diffusion susceptibility tests were performed for E. coli strain BW25113 and 10 isogenic derivatives carrying the most prevalent LLFR chromosomal mutations (∆uhpT, ∆glpT, ∆cyaA, and ∆ptsI) and their double combinations. Whereas standard G6P concentrations detected only ∆uhpT single and double variants, assays with reduced G6P detected all LLFR variants. In addition, G6P levels were determined to be ≤5 µg/mL in urine samples from 30 patients with urinary tract infection (UTI) caused by E. coli and 10 healthy volunteers, suggesting that most bacterial cells in uncomplicated UTIs are facing fosfomycin under low G6P concentration. Reducing G6P allows for the detection of LLFR variants, which may suppose a risk for future resistance development, especially in UTIs.